PSIKOEDUKASI PENINGKATAN PERAN BYSTANDER UNTUK MENGURANGI BULLYING DI PONDOK PESANTREN - Farizan Adani, Erizza; Firdaus Nuryananda, Tirta; Nuril Mukminin, Muhammad; Nurma Halida, Arfin; Nurwidawati, Desi; Ratna Brillianti Kusnanda, Raniah; Ulimazeta , Adnin (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2026)
The issue of bullying at Al Fattah Global Islamic School (GIBS) Boarding School has become a major concern in efforts to create a safe and supportive learning environment. One of the issues identified is the low involvement of students as bystanders in preventing and stopping bullying. Students tend to be passive and lack the knowledge and courage to take action. The aim of this activity is to provide psychoeducation to students about bullying, its impacts, and concrete strategies for active and effective bystanders. The program was implemented through a series of stages, including the preparation of modules, coordination with partners, and the implementation of interactive training in the form of lectures, educational videos, and discussions. This activity involved students from grades 7 to 12 at GIBS. The results of the activity showed a significant increase in participants' understanding and awareness of the concept of bullying and the importance of the active role of bystanders. Participants' knowledge increased overall, particularly regarding the impact of bullying on victims and concrete steps that bystanders can take. In conclusion, psychoeducation has proven effective in enhancing the social empowerment of students to engage in bullying prevention and contributes to the creation of a pesantren culture that prioritizes empathy, solidarity, and psychosocial safety. ABSTRAK Permasalahan bullying di Pondok Pesantren Al Fattah Global Islamic School (GIBS) menjadi perhatian utama dalam upaya menciptakan lingkungan belajar yang aman dan mendukung. Salah satu isu yang diidentifikasi adalah rendahnya keterlibatan santri sebagai bystander dalam mencegah dan menghentikan bullying. Santri cenderung pasif dan kurang pengetahuan serta keberanian untuk bertindak. Tujuan dari kegiatan ini adalah untuk memberikan psikoedukasi kepada santri mengenai bullying, dampaknya, serta strategi konkret bagi bystander yang aktif dan efektif. Program ini diimplementasikan melalui serangkaian tahapan yang meliputi penyusunan modul, koordinasi dengan mitra, dan pelaksanaan pelatihan interaktif berupa ceramah, video edukasi, dan diskusi. Kegiatan ini melibatkan santri dari kelas 7 hingga 12 di GIBS. Hasil dari kegiatan ini menunjukkan adanya peningkatan signifikan dalam pemahaman dan kesadaran peserta terhadap konsep bullying dan pentingnya peran aktif bystander. Pengetahuan peserta meningkat secara keseluruhan, terutama dalam hal dampak bullying terhadap korban dan langkah-langkah konkret yang dapat diambil oleh bystander. Kesimpulannya, psikoedukasi terbukti efektif dalam meningkatkan keberdayaan sosial santri untuk terlibat dalam pencegahan bullying, serta berkontribusi pada terciptanya budaya pesantren yang mengedepankan empati, solidaritas, dan keamanan psikososial.